(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article examines the key distinctions between the Flipped Classroom model and traditional instructional approaches, highlighting differences in pedagogical principles, classroom dynamics, and student-teacher roles. Supported by scholarly literature, this comparison provides a framework for educators considering a transition to more student-centered methodologies.